High resolution mapping of QTLs for fruit color and firmness in Amrapali/Sensation mango hybrids - Srivastav, Manish; Radadiya, Nidhi; Ramachandra, Sridhar; Jayaswal, Pawan Kumar; Singh, Nisha; Singh, Sangeeta; Mahato, Ajay Kumar; Tandon, Gitanjali; Gupta, Ankit; Devi, Rajni; Subrayagowda, Sreekanth Halli; Kumar, Gulshan; et al. (Frontiers in Plant Science, 2023)
Mango (Mangifera indica L.) acclaimed as the ‘King of fruits’ in the tropical world has historical, religious, and economic values. It is grown commercially in more than 100 countries and fresh mango world trade accounts for ~3,200 million US dollar. Mango is widely cultivated in sub-tropical and tropical regions of the world with India, China, and Thailand being the top three producers. Mango fruit is adored for its taste, color, flavor, and aroma. Fruit color and firmness are important fruit quality traits for consumer acceptance but their genetics are poorly understood. For genetic mapping of these traits’ mango varieties Amrapali and Sensation having contrasting fruit quality traits were crossed for the development of a mapping population. Ninety-two bi-parental progenies obtained from this cross were used for the construction of a high-density linkage map and identification of QTLs. Genotyping was carried out using a 80K SNP chip array. Initially, we constructed two high-density linkage maps based on the segregation of female and male parents. Female map was with 3,213 SNPs and the male map with 1,781 SNPs distributed on 20 linkages groups covering the map lengths of 2,844.39 and 2,684.22cM, respectively. Finally, the integrated map comprised 4,361 SNP markers distributed on 20 linkage groups that consisted of the chromosome haploid number in Mangifera indica (n = 20). The integrated genetic map covered the entire genome of Mangifera indica ¬cv. Dashehari, with a total genetic distance of 2,982.75 cM and an average distance between markers of 0.68 cM. The length of LGs varied from 85.78 to 218.28 cM, with a mean size of 149.14 cM. Phenotyping for the fruit color and firmness traits was done for two consecutive seasons. We identified important consistent QTLs for 12 out of 20 traits with integrated genetic linkages having significant LOD scores in at least one season. Important QTLs for fruit peel color are located at Chr 2, 3, 4, 10, 12, 14, 15, 17 and 18, and firmness on Chr 3, 4, 6, 11, 19 and 20. The QTLs mapped in this study would be useful in the marker-assisted breeding of mango for improved efficiency.